2015
DOI: 10.13189/ujer.2015.031111
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Modified Soft Skills Assessment Instrument (MOSSAI) for Use in Nigeria

Abstract: Currently, it has become an accepted norm nearly all over the globe to teach and assess soft skills. However, in Nigeria, it is an emerging area of interest that needs to be addressed squarely. In the light of the foregoing , this study validated a modified version of Measuring and Assessment Soft Skills (MASS) (an instrument developed and used by twenty European researchers from five countries), for use in the Nigeria setting. It was administered on a randomly selected sample from the northern and southern pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…This study recommends also the consideration for instituting a soft skill certification program. As much as cognitive skills are assessed and students are awarded certificates, soft skills should also be assessed, and certificates should be awarded to senior secondary students to promote practical application of soft skill among students and teachers (Aworanti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study recommends also the consideration for instituting a soft skill certification program. As much as cognitive skills are assessed and students are awarded certificates, soft skills should also be assessed, and certificates should be awarded to senior secondary students to promote practical application of soft skill among students and teachers (Aworanti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our existing framework, we use similar tools to assess technical and soft skills, which may not be worthwhile. It has generally been observed that, where technical skills are easy to assess, soft skills are difficult to assess [22,23]. To this end, more innovative methods will be explored to assess and evaluate soft skills in a more systematic manner.…”
Section: Discussionmentioning
confidence: 99%
“…The test comprised of open-ended and closed-ended questions and some asked the respondent to put a tick under not appropriate, (NA), appropriate (A), or very appropriate (VA) to show their opinion. Furthermore, question three and four of the test in the attached Appendix A was adapted from a validation of modified soft skills assessment instrument (MOSSAI) (Aworanti et al, 2015). Items in question five (Appendix A) of the test were adapted from the reformed teaching observation protocol (RTOP) (Piburn et al, 2000).…”
Section: Instrumentmentioning
confidence: 99%